The great panic: the bankruptcy of finance companies in Costa Rica in the eighties - Agüero García, Javier (2021)
This current situation study, based on a review of journalistic sources, addresses, from a perspective of the recent past, a set of episodes that generated a panic that invaded the Costa Rican population as a result of the bankruptcy of financial companies from 1987; private entities in charge of attracting resources from savers who were paid hefty interest above those offered by public banks. First, a contextualization of the decade is elaborated, to recognize the particularities of the eighties; secondly, the characterization of the advertising of these businesses is given, in order to know the main focuses for attracting savers. Finally, the series of company bankruptcies is analyzed, in order to identify the main milestones, typical of the stock market crash. It concludes with the recognition of a tremendously complex situation, immersed in the last part of the eighties.